The historical evolution of employee engagement and self-efficacy constructs - Dagher, Grace K. (2015)
Purpose – This paper aims to highlight the historical roots of employee engagement and empirically examine the influence of self-efficacy on the three dimensions of employee engagement (vigor, dedication and absorption). Design/methodology/approach – A sample of 426 male and female respondents in the service industry from Lebanon was surveyed using a multi-scale measure composed of 25 items. Regression analysis was used to test the data for the hypothesized relationships between the variables. Findings – History of management continues to be the backbone of the so-called modern concepts. Although the term employee engagement was not used in scientific management or in the human relations movement, the characteristics were incorporated in these early schools. The three factors of employee engagement explained 78 per cent of the total variance of employee engagement construct and were significantly influenced by self-efficacy. Research limitations/implications – The first limitation of this study is the self-reported data, and the second limitation is the source from one industry (service), although different organizations were incorporated. Caution is advised against generalizations of the findings. Practical implications – The results of this study provide insights for both researchers and managers to better understand the relationship between three dimensions of employee engagement and self-efficacy from a non-Western context. The belief in one’s own capabilities helps promote employee engagement. Social implications – Lebanon offers an interesting context; it is considered as the only Arab country that provides an interaction between the Western and Middle Eastern countries. Originality/value – This study aimed to trace the historical roots of employee engagement to the early management schools. Moreover, studies similar to the present investigation exist; however, this is the first time that a non-Western Arab sample was used to examine the influence of self-efficacy on the three dimensions of employee engagement.